Characteristics of a walking simulator with parallel manipulators - Elías, D.; Callupe, R.; Ceccarelli, M. (Kluwer Academic Publishers, 2015)
In this paper an on-site walking simulator with parallel manipulators is presented by looking at characteristics of a prototype built in Lima, Perú. Design peculiarities of parallel architectures are used for a powerful precise walking simulator by combining Kinematic features with dynamic capabilities through a suitable control system.
Keywords: Kinematics; Simulation; Computer science; Motion simulator; Parallel manipulator; Control engineering; Robot; Engineering; Artificial intelligence; Motion (physics); Physics; https://purl.org/pe-repo/ocde/ford#2.02.02